Prolonged Exposure (PE) for Treatment of Childhood Sexual Abuse-Related PTSD: Do We Need to Augment It? - Hembree, Elizabeth A.; Brinen, Aaron P. (Pragmatic Case Studies in Psychotherapy, 2009)
Kramer's thoughtful and extremely thorough case study of treating Caroline, a survivor of childhood sexual abuse (CSA), raises several important issues. A major assumption underlying Kramer's approach with Caroline's PTSD symptoms is that the Prolonged Exposure (PE) manualized treatment of Foa and her colleagues is a necessary but not sufficient method to address the clinical needs of such a client. Thus Kramer begins his treatment of this client with other clinical components, such as an assessment of Caroline's interpersonal patterns utilizing Caspar'sPlan Analysis method; custom tailoring of his therapeutic relationship with Caroline; imaginative relaxation; cognitive crisis intervention; and interventions to enhance the client's social competence. He then initiates a brief course of in vivo and imaginal exposure, following the procedures in the PE manual. In this commentary, we critically evaluate this major assumption of Kramer's and review data which argue that PE can be sufficient for treating clients like Caroline. Specifically, our commentary considers the following questions: (a) What are the effects of exposure alone versus exposure combined with other treatments for PTSD? (b) Does CSA-related PTSD require additional treatment components other than PE? (c) Is PE intolerable without additional interventions? (d) Why is length of treatment important? and (e) What are some of the issues raised by the manner in which Kramer implemented the PE treatment?